SOME TECHNIQUES TO UTILIZE ELECTRONIC AND NON-ELECTRONIC DICTIONARIES FOR TEACHING ENGLISH TO SENIOR HIGH SCHOOL STUDENTS - Zurnelly, Netty (Reflective, 2013)
One way to trace the wordsâ meaning, part of speech, and the phonetic transcription is by looking for into dictionary. Yet, it is not that simple since every dictionary has its own characteristics. Training in using dictionaries is very essential especially to senior high school students who are potentially use either electronicdictionary or non-electronic dictionary. Unfortunately, in most classrooms very little time is provided to specifically âteachâ students on how to maximize the use of dictionary. This article proposes some techniques to be applied by senior high school students in Indonesia to maximize the potential of every type of dictionary.Keywords : dictionary, electric, non-electric, senior high school students